Campus Radio Against Conflict: The Case Study in The University of Peshawar - Irfan Ashraf, Syed (Jurnal Komunikasi Islam, 2014)
This study deals with the role of Campus Radio (CR) of Peshawar University in Pakistan both to on campus community and off campus community related to the cases following the 9/11 such as terror and incident toward the cause of the ousted Afghan Taliban militant. The study uses qualitative research method to provide relevant information based on the actual participation, observations, and direct interviews of the researcher. Pashto language programs overcome the rupture caused by terrorism through suturing the past to the present. This “linking strategy” provides cathartic opening for the off-campus community, helping them to question temporal realities-radicalism and terrorism.Keywords: Campus radio, Peshawar university, conflict, qualitative method----------------------------------------------------------------------Studi ini membahas peran Radio Kampus, Universitas Peshawar, Pakistan bagi komunitas di dalam dan komunitas di luar kampus terkait dengan insiden terguling–nya militan Afghanistan dan kasus-kasus teror setelah peris–tiwa serangan 9/11. Penelitian ini menggunakan metode kualitatif untuk memberikan informasi yang relevan berda–sarkan partisipasi langsung, pengamatan, dan wawancara. Hasil penelitian ini menyatakan bahwa program bahasa Pashto menyelesaikan problem yang disebabkan oleh tero–risme melalui menghubungkan masa lalu dengan masa kini, yang disebut dengan “linking strategy”. Strategi ini membe–rikan ruang katarsis bagi masyarakat luar kampus, serta membantu mereka untuk mengkritisi realitas radikalisme dan terorisme yang ada.Kata Kunci: Radio kampus, Universitas Peshawar, konflik, metode kualitatif